PROFILE CHARACTERISTICS OF THE SELECTED FARMERS OF SEED VILLAGE PROGRAMME (SVP) WITH REFERENCE TO RICE CROP - and D. SRINIVASA CHARY, GOTTEMUKKULA BHAVANI, M. SREENIVASULU, V. RAVINDER NAIK G. E.CH. VIDYA SAGAR (The Journal of Research, PJTSAU, 2020)
Seed is the critical input in sustainable development of agriculture for enhancing production and productivity. As seed quality is one of the key contributors to crop productivity and food production a robust seed system is most significant for food security in India. The present investigation was carried out in Telangana State. Ex-post facto research design was followed selecting 120 respondents at random from three districts, three mandals and three villages of the mandal. The profile characteristics of respondents of SVP practicing seed production in rice crop was studied on adopting Ex-post facto research design. Salient findings of the study are, most of the respondents were middle aged (67.50%), had high school level education (34.16%), with marginal land holding (49.16%), low farming experience (46.66%), medium extension contact (42.50%), medium mass media utilization (45.00%), medium storage facilities (56.66%), medium market orientation (42.5%), medium innovativeness (59.16%), medium aspirational level (52.50%), high economic motivation (42.50%) and medium risk orientation (51.66%).